Compare the physicochemical and biological properties of engineered polymer-functionalized silver nanoparticles against Porphyromonas gingivalis - Zhang, Meng; Lo, Edward C. M. (Frontiers in Microbiology, 2022)
Background: Some polymer-functionalized AgNPs (P-AgNPs) have been developed to optimize the biological properties of AgNPs. However, there are no studies in the literature comparing the differences in physicochemical and biological properties of AgNPs caused by various polymer-functionalizations and providing evidence for the selection of polymers to optimize AgNPs. Methods: Two AgNPs with similar nano-size and opposite surface charges were synthesized and functionalized by seven polymers. Their physicochemical properties were evaluated by UV-Visible absorption, dynamic light scattering, transmission electron microscopy and inductively coupled plasma optical emission spectroscopy. Their biological properties against Porphyromonas gingivalis and human gingival fibroblast were investigated by MIC determination, time-dependent antibacterial assay, antibiofilm activity and cell viability assay. Silver diamine fluoride, AgNO3 and metronidazole were used as positive controls. Results: Comparative analysis found that there were no significant differences between P-AgNPs and AgNPs in nano-size and in surface charge. Raman spectroscopy analysis provided evidence about the attachment of polymers on AgNPs. For antibacterial property, among the negatively charged AgNPs, only polyvinylpyrrolidone (PVP)-functionalized AgNPs-1 showed a significant lower MIC value than AgNPs-1 (0.79 vs 4.72 μg/mL). Among the positively charged AgNPs, the MIC values of all P-AgNPs (0.34-4.37 μg/mL) were lower than that of AgNPs-2 (13.89 μg/mL), especially PVP- and Pluronic127-AgNPs-2 (1.75 and 0.34 μg/mL). For antibiofilm property, PVP-AgNPs-1 (7.86 μg/mL, P=0.002) and all P-AgNPs-2 (3.42-31.14 μg/mL, P<0.001) showed great antibiofilm effect against Porphyromonas gingivalis biofilm at 5* to 10*MIC level. For cytotoxicity, all negatively charged AgNPs and PVP-AgNPs-2 showed no cytotoxicity at MIC level, but significant cytotoxicity was detected at 2.5* to 10*MIC levels. Conclusions: Among the polymers studied, polymer functionalization does not significantly alter the physical properties of AgNPs, but modifies their surface chemical property. These modifications, especially the functionalization of PVP, contribute to optimize the antibacterial and antibiofilm properties of AgNPs, while not causing cytotoxicity at the MIC level.